Chemistry of 2-(2′-Aminophenyl)benzothiazole Derivatives: Syntheses, Photophysical Properties and Applications - Ekaterina K. Pylova; Taisiya S. Sukhikh; Alexis Prieto; Florian Jaroschik; Sergey N. Konchenko (Molecules)
2-(2′-aminophenyl)benzothiazole is a readily tunable fluorescent core with widespread applications in coordination chemistry, sensing, light-emitting processes, medicinal chemistry, and catalysis. This review provides an overview of the synthetic methodologies to access 2-(2′-aminophenyl)benzothiazole and its organic derivatives, including various phosphorous and silane pincer ligands. The luminescent properties will be discussed, with a special focus on ESIPT and AIE processes. The coordination of transition metals and lanthanides is presented, as well as their influence on biological and light-emitting properties. 2-(2′-aminophenyl)benzothiazole derivatives have also been employed as sensors for a range of cations and anions due to their various binding modes, as well as for bioimaging purposes. Recently, the first application in photocatalysis has emerged, showing one of the many openings for these organic building blocks in the future.